THE RELATIONSHIP OF THE TREATMENT OUTCOME OF THE SEASONAL FORM OF ALLERGIC RHINITIS IN CHILDREN WITH THE INITIAL VEGETATIVE TONE OF THE BODY - Arifov, S.S.; Daliev, A.G.; Tuychiev, G.U.; Gulomov, Sh.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: Assessment of the effectiveness of treatment of seasonal allergic rhinitis, taking into account the state of the initial vegetative tone of the body in children of an older age group. Material and methods: Under observation, there were 74 children with allergic rhinitis at the age of 12-18 years, of which 31 (41.9%) were girls and 43 (58.1%) were boys. The control group consisted of 25 healthy children. The diagnosis was established on the basis of complaints, medical history, results of clinical and allergological studies. Results: As observations have shown, there is a relationship between the results of pharmacotherapy and the initial autonomic tone of the child’s body. In 25.6% of children with seasonal allergic rhinitis with vagotonia, an additional “enhanced” treatment regimen was required to achieve clinical recovery. Conclusions: The prevalence of the parasympathetic orientation of the initial vegetative tone is facilitated by vagotonia, which ultimately causes a more stubborn manifestation of the clinical symptoms of the disease.